Screening Modernity:: Cinema and Sexuality in Ann-Marie MacDonald’s Fall On Your Knees - Rifkind, Candida (Studies in Canadian Literature / Études en littérature canadienne, 2002)
In Fall on Your Knees, Ann-Marie MacDonald writes early twentieth-century Cape Breton and New York through attention to the popular culture of the era, particularly in aspects of the visual, including paintings, photographs, and films. Just as the female characters trangress boundaries between normative and queer sexuality, so too the text offers an aesthetic queering of the boundaries between representational media. The representations of 1920s film star Louise Brooks, particularly, guide readers to a supplemental set of cultural meanings carried by her image and to a recognition that representation, like history, is always partial.